2006
DOI: 10.1097/01.ta.0000225925.53583.27
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Management Program Reduces Transfusion Volumes, Incidence of Ventilator-Associated Pneumonia, and Cost in Trauma Patients

Abstract: An anemia management program appears to be safe when applied in the acute ICU phase of trauma care. Implementation of AMP in the ICU reduced the volume of PRBCs transfused with significant cost savings. No significant differences in length of stay, mortality rate, or MI rate were seen. The significant decrease in the rate of VAP requires further elucidation. Further long-term and larger studies are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…In another study about the effect of air pollution and anaemia on the rate of pneumonia hospitalization, anaemia in adjunctive with air pollution was found to increase the rate of hospitalization while air pollution in non-anaemic patients did not affect the rate of pneumonia hospitalizations [25]. Earley et al revealed that application of anaemia management programme in ICU reduced the complication rate of ventilator acquired pneumonia [26].…”
Section: Discussionmentioning
confidence: 97%
“…In another study about the effect of air pollution and anaemia on the rate of pneumonia hospitalization, anaemia in adjunctive with air pollution was found to increase the rate of hospitalization while air pollution in non-anaemic patients did not affect the rate of pneumonia hospitalizations [25]. Earley et al revealed that application of anaemia management programme in ICU reduced the complication rate of ventilator acquired pneumonia [26].…”
Section: Discussionmentioning
confidence: 97%
“…McIntyre et al 68 found, in a randomized controlled trial (RCT), no changes in mortality, MOF or length of stay using a transfusion trigger of 7 mg/dL in trauma patients (n Ď­ 203). Earley et al 69 saw in a retrospective investigation of trauma patients no increase in mortality or length of stay after reducing the transfusion trigger to 7 mg/dL, but a significant decrease of ventilator-associated pneumonia (n Ď­ 514, p Ď˝ 0.002) and a decrease in hospital cost of about $236 per patient. The available data supports a reduced transfusion trigger of 7 mg/dL in trauma patients.…”
Section: Therapeutic Consequencesmentioning
confidence: 96%
“…RBCT also is an independent risk factor for impaired pulmonary function and prolonged ventilator support, acute lung injury, acute respiratory distress syndrome (ARDS) [84,85], systemic inflammatory response syndrome [83,86], renal dysfunction [87], multiple organ failure or dysfunction [34,88,89], transfusion reactions [39], and increased length of stay [33]. In SAH patients, RBCT has also been associated with medical complications and infection [29,57].…”
Section: Rbct In General Medical and Surgical Critical Carementioning
confidence: 98%
“…In general critical care patients, RBCT is associated with complications such as immunosuppression, transmission of infectious agents, postoperative infections, and pneumonia [77][78][79][80][81][82][83]. RBCT also is an independent risk factor for impaired pulmonary function and prolonged ventilator support, acute lung injury, acute respiratory distress syndrome (ARDS) [84,85], systemic inflammatory response syndrome [83,86], renal dysfunction [87], multiple organ failure or dysfunction [34,88,89], transfusion reactions [39], and increased length of stay [33].…”
Section: Rbct In General Medical and Surgical Critical Carementioning
confidence: 99%